PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GUNUNG SUMBER MURNI, JAKARTA - Rahma Suci, Tiara; Chasanah, Uswatun (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the effect of work motivation and work discipline on employee performance at PT Gunung Sumber Murni Jakarta. The method used is quantitative. The sampling technique uses saturated sampling and in this study sample amounted to 55 respondents. Data analysis uses tests of validity, reliability, classical assumptions, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests. The result of this study is that work motivation has a significant effect on employee performance with a simple linear regression equation Y = 23.705 + 0.463X1, a correlation value of 0.780 means that the two variables have a strong level of relationship. The value of the coefficient of determination is 60.9%. Test the hypothesis obtained t count > t table or (9.089>1.988). Thus H0 is rejected and H1 is accepted, meaning that there is a significant effect of work motivation on employee performance. Work discipline has a significant effect on employee performance with a simple linear regression equation Y = 24.464 + 0.438X2, a correlation value of 0.825 means that the two variables have a very strong level of relationship. The value of the coefficient of determination is 68%. Test the hypothesis obtained t count > t table or (10.615>1.988). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant influence of work discipline on employee performance. Work motivation and work discipline have a significant effect on employee performance with multiple linear regression equations Y = 19.332 + 0.309X1+0.266X2, a correlation value of 0.776 meaning that the two variables have a strong level of relationship. The value of the coefficient of determination is 77.6% while the remaining 22.4% is influenced by other factors. Test the hypothesis obtained F count > F table or (94.515 > 3.158). Thus H0 is rejected and H3 is accepted, meaning that there is a simultaneous significant effect of work motivation and work discipline on employee performance.